Implementation of the 2023 Community Service Lecture (CSL) for STIT Muhammadiyah Abdya Students in Two Regencies: Synergy of Education and Community Empowerment - Razie, T. Fachrul; Baidullah, Baidullah; Abidin, Zainal; Authar, Tanzilul; Abdillah, Zakie; Musbir, Musbir (STMIK Indonesia Banda Aceh, 2026)
Community Service Lecture (CSL) activities are an integral part of the implementation of the Tri Dharma of Higher Education, especially in the aspect of community service. This program was implemented by STIT Muhammadiyah Aceh Barat Daya in 2023 in two locations, namely Central Aceh Regency and Southwest Aceh Regency, with the theme